Holographic p-wave superfluid with Weyl corrections - Huang, YongHao; Pan, QiYuan; Qian, Wei-Liang [UNESP]; Jing, JiLiang; Wang, ShiLiang (Science Press, 2020)
In this work, we study the effects of the Weyl corrections on the p-wave superfluid phase transition in terms of an Einstein-Maxwell theory coupled to a complex vector field. In the probe limit, it is observed that the phase structure is significantly modified owing to the presence of the higher order Weyl corrections. The latter, in general, facilitates the emergence of the superfluid phase as the condensate increases with the Weyl coupling measured by gamma. Moreover, several features about the phase structure of the holographic superfluid are carefully investigated. In a specific region, the phase transition from the normal phase to the superfluid phase is identified to be the first order, instead of being the second order, as in the cases for many holographic superconductors. By carrying out a numerical scan of model parameters, the boundary dividing these two types of transitions is located and shown to be rather sensitive to the strength of Weyl coupling. Also, a feature known as Cave of Winds, associated with the emergence of a second superfluid phase, is observed for specific choices of model parameters. However, it becomes less prominent and eventually disappears as gamma increases. Furthermore, for temperature in the vicinity of the critical one for vanishing superfluid velocity, denoted by T-0, the supercurrent is found to be independent of the Weyl coupling. The calculated ratio, of the condensate with vanishing superfluid velocity to that with maximal superfluid velocity, is in good agreement with that predicted by Ginzburg-Landau theory. While compared with the impact on the phase structure owing to the higher curvature corrections, the findings in our present study demonstrate entirely different characteristics. Further implications are discussed.
Keywords: AdS; CFT correspondence; Weyl corrections; holographic superfluid